THE POLITICAL ROLE OF CRIMINAL LAW IN SHAPING COUNTER-TERRORISM POLICY IN INDONESIA - Patria, Widya Nusa; Shodiq, Md.; Rattanapun, Supot (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
The politics of criminal law has a strategic role in shaping counter-terrorism policy in Indonesia, especially after the increasing threat of global and domestic terrorism. Through Law Number 5/2018, the state adopts a more repressive criminal law approach by expanding the definition of terrorism crimes and giving greater authority to security forces. This research aims to analyze the role of criminal law politics in the process of counter-terrorism policy formation, as well as evaluate its suitability with the principles of justice and the rule of law. By using a normative juridical approach and qualitative analysis of legislation, doctrine, and the dynamics of policy formation, this research finds that counter-terrorism policies in Indonesia still tend to favor the security paradigm over the protection of human rights. The politics of Indonesian criminal law has not fully demonstrated alignment with substantive justice, due to weak accountability mechanisms and limited space for public participation in policy formulation. This research provides a theoretical contribution in expanding the understanding of the relationship between political power and criminal law, as well as encouraging policy reforms that are more democratic, proportional, and based on human rights values.